EuReCa_Serbia Subotica 2014-2021. Epidemiology of Out-of-Hospital Cardiac Arrest - Budimski Soldat, Mihaela; Momirović Stojkovic, Milena (Journal Resuscitatio Balcanica, 2024)
Aims and goals Continuous monitoring of epidemiology, treatment and outcome of out of hospital cardiac arrest on the territory of Subotica municipality. Methodology EuReCa Serbia is a part of international, prospective, multicentric, EuReCa_One project, which records survival of patients (epidemiology, treatment, outcome) with out of hospital cardiac arrest in Europe, who are registered on „clinicaltrials.gov (registration number: NCT02236819) by ERC. Data gathered by research center Subotica from October 1, 2014 to December 31, 2021. have been observed. Statistical software SPSS Statistics for Windows v27.0 was used for analysis. Variables are presented through incidence and percentage, and Chi-Square test was used for connection testing between categorical variables. Results During the observed time period, the incidence of EuReCa events was 171,67/100.000. Annual incidence of initiated cardiopulmonary resuscitation was 60.75/100000. Age Median for both sexes was 71 (IQR 62-81). Incidence of out of hospital cardiac arrest in patients“ residences, per year, was 157.08 /100.000. Yearly Incidence of provided basic life support was 11.07. Return of spontaneous circulation (ROSC) was achieved in 164 patients of 516 cases (31.78%), which makes the incidence of achieved ROSC, per year, 19.31/100 000. Conclusion Incidence of initiated cardiopulmonary resuscitation and achieved return of spontaneous circulation can be compared with results of european countries. Further monitoring of OHCA is necessary so that the reasons for poor laymen involvement can be determined.